Preclinical evaluation of efficacy and safety of an improved lentiviral vector for the treatment of β-thalassemia and sickle cell disease - Negre, Olivier; Bartholomä, Cynthia C.; Deichmann, Annette; Fronza, Raffaele; Schmidt, Manfred; Kalle, Christof von (Current gene therapy, 2015)
A previously published clinical trial demonstrated the benefit of autologous CD34[+] cells transduced with a self-inactivating lentiviral vector (HPV569) containing an engineered β-globin gene (β[A-T87Q] -globin) in a subject with β-thalassemia ...
Gesehen am 17.08.2020